2016
DOI: 10.1128/jvi.03035-15
|View full text |Cite
|
Sign up to set email alerts
|

During Infection, Theiler's Virions Are Cleaved by Caspases and Disassembled into Pentamers

Abstract: Infected macrophages in spinal cords of mice persistently infected with Theiler's murine encephalomyelitis virus (TMEV) undergo apoptosis, resulting in restricted virus yields, as do infected macrophages in culture. Apoptosis of murine macrophages in culture occurs via the intrinsic pathway later in infection (>10 h postinfection [p.i.]) after maximal virus titers (150 to 200 PFU/ cell) have been reached, with loss of most infectious virus (<5 PFU/cell) by 20 to 24 h p.i. Here, we show that BeAn virus RNA repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Similarly, in vitro studies demonstrate a restricted virus replication in TMEV-infected microglia, whereas astrocytes produce high amounts of viral RNA and antigen [54]. The induction of apoptosis represents a mechanism to restrict virus replication because TMEV virions are cleaved by executioner caspases, such as caspase-3, disassembling virions into pentamers [55]. Astrocytes are relatively resistant to TMEV-induced apoptosis, whereas neurons are predominantly affected by apoptotic cell death during acute polioencephalomyelitis [41,56,57].…”
Section: Virus Tropism and Spreadmentioning
confidence: 99%
“…Similarly, in vitro studies demonstrate a restricted virus replication in TMEV-infected microglia, whereas astrocytes produce high amounts of viral RNA and antigen [54]. The induction of apoptosis represents a mechanism to restrict virus replication because TMEV virions are cleaved by executioner caspases, such as caspase-3, disassembling virions into pentamers [55]. Astrocytes are relatively resistant to TMEV-induced apoptosis, whereas neurons are predominantly affected by apoptotic cell death during acute polioencephalomyelitis [41,56,57].…”
Section: Virus Tropism and Spreadmentioning
confidence: 99%
“…While morphologic changes like membrane blebbing are hallmarks of apoptotic cell death [44,45] and play a key role in facilitating the disassembly of dying cells [10,11], the molecular regulators and the function of this process are not fully defined [4]. Understanding the mechanistic basis of apoptotic cell disassembly is important especially as the formation of ApoBDs have been implicated in various disease settings including inflammation [8], infection [46], atherosclerosis [47] and autoimmunity [5,6,48]. In this study, using both pharmacologic and genetic approaches, we have shown that ROCK1 but not PAK2 or LIMK1 is a key positive regulator of apoptotic membrane blebbing and ApoBD formation in selected number of cell types.…”
Section: Discussionmentioning
confidence: 99%
“…97 The penton capsomere proteins of the Theiler's murine encephalomyelitis virus (TMEV) are cleaved by caspase-3 activity, but the direct effect of this cleavage on viral replication is unclear. 98 The nucleoprotein (NP) of Junin Virus is cleaved by caspase-3. Interestingly, expression of NP suppresses the activity of caspase-3 in camptothecin-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…The penton capsomere proteins of the Theiler's murine encephalomyelitis virus (TMEV) are cleaved by caspase-3 activity, but the direct effect of this cleavage on viral replication is unclear. 98 …”
Section: Discussionmentioning
confidence: 99%